Shonen note : boy soprano. 3 - Kamatani, Yuhki (Kodansha USA Publishing, LLC, 2023)
"Russian boy soprano Vladimir Popov is touring Japan when he learns about Yutaka's amazing talent. He insists on meeting this new rival and hearing him sing, but when he watches a rehearsal of The Turn of the Screw, he doesn't mince words in telling Yutaka how he feels about the performance... Will his encounter with Vladimir be a blow to Yutaka's confidence, or will it give him the strength to continue to press onward, in both the opera and school choir?"--